Medium-density fibreboards bonded with phenol-formaldehyde resin and calcium lignosulfonate as an eco-friendly additive. Issue 1 (2nd January 2021) - Antov, Petar; Savov, Viktor; Mantanis, George I.; Neykov, Nikolay
ABSTRACT: The potential of addition of calcium lignosulfonate as an eco-friendly additive with a phenol-formaldehyde (PF) resin, at different ratios, to produce medium-density fibreboards (MDF) with acceptable properties, was investigated in this work. The fibreboards were fabricated in the laboratory with low PF resin percentage (3%, 4%, 5%), while the addition levels of calcium lignosulfonate varied from 5% to 15% (on the dry fibres). The physical and mechanical properties of the fibreboards were evaluated, and further statistically analysed in order to determine the optimal values of PF resin content and lignosulfonate addition for fulfilling the European standards. It was shown that at the low PF resin content (3%), addition of lignosulfonate should not exceed 10% to avoid deterioration in the mechanical properties. It was concluded that PF resin content of 3.5% can be recommended for the production of lignosulfonate-PF bonded MDF panels to comply with the EN standard requirements.